Biomass-specific rates as key performance indicators: A nitrogen balancing method for biofilm-based electrochemical conversion - Winkelhorst, Marijn; Cabau-Peinado, Oriol; Straathof, Adrie J.J.; Jourdin, Ludovic (Frontiers in Bioengineering and Biotechnology, 2023)
Microbial electrochemical technologies (METs) employ microorganisms utilizing solid-state electrodes as either electron sink or electron source, such as in microbial electrosynthesis (MES). METs reaction rate is traditionally normalized to the electrode dimensions or to the electrolyte volume, but should also be normalized to biomass amount present in the system at any given time. In biofilm-based systems, a major challenge is to determine the biomass amount in a non-destructive manner, especially in systems operated in continuous mode and using 3D electrodes. We developed a simple method using a nitrogen balance and optical density to determine the amount of microorganisms in biofilm and in suspension at any given time. For four MES reactors converting CO2 to carboxylates, >99% of the biomass was present as biofilm after 69 days of reactor operation. After a lag phase, the biomass-specific growth rate had increased to 0.12-0.16 d-1. After 100 days of operation, growth became insignificant. Biomass-specific production rates of carboxylates varied between 0.08-0.37 molC molx-1d-1. Using biomass-specific rates, one can more effectively assess the performance of MES, identify its limitations, and compare it to other fermentation technologies.